LIFE JACKET DESIGN AS SELF PROTECTION FOR TRADITIONAL FISHERMAN - Citra Indah Asmarawati; Bahariandi Aji Prasetyo (Journal of Industrial Engineering Management, 2023)
One of the personal protective equipment that fishermen must have is a life jacket. The existing life jackets basically comply with government regulations such as being brightly colored, able to float and have a whistle. However, the price of life jackets is considered relatively expensive, so fishermen often choose not to use or buy used life jackets. Materials for life jackets such as Neoprene, Nylon, and Polyester have varying characteristics and are adapted to the environment in which they are used. Implementation of RFID technology in life jackets increases identification efficiency and safety management in waters. The yellow color of the life jacket improves visibility in the water, especially in low light. The dimensions of the life jacket are informed by anthropometric studies, with an innovative design that allows development when needed. Assembly design efficiency shortened assembly time from 13201 to 5110 minutes through design improvements.